Social Inequalities and Occupational Stratification Methods and Concepts in the Analysis of Social Distance - Lambert, Paul (Palgrave Macmillan UK, 2018)
This book explores how structures of social inequality are linked to the social connections that people hold. The authors focus upon occupational inequalities where they see, for example, that the typical friendship patterns of people from one occupation are often very different to those of people from another. Social Inequalities and Occupational Stratification leverages empirical data about differences in social connections to chart structures of social distance and social inequality. Several of its chapters provide coverage of the long-standing CAMSIS project and its approach to analysing social interaction patterns in terms of a single dimension related to social inequality. Lambert and Griffiths also explore different ways that statistical methods and tools of social network analysis can be used to study the relationship between social distance and social stratification. .